To find the horizontal asymptote of the function \( g(x) = \frac{1}{x} + 23 \), we need to analyze the behavior of the function as \( x \) approaches infinity (or negative infinity).
-
As \( x \to \infty \): \[ g(x) = \frac{1}{x} + 23 \to 0 + 23 = 23 \]
-
As \( x \to -\infty \): \[ g(x) = \frac{1}{x} + 23 \to 0 + 23 = 23 \]
In both cases, the function approaches the value 23. Therefore, the horizontal asymptote of the graph of \( g(x) \) is:
\[ y = 23 \]
So the equation of the horizontal asymptote is \( \boxed{23} \).